The Formation of Skills and Abilities Influencing School Performance Between Late Nursery School and Early School Age (Training and Practice : Journal of Educational Sciences, 2017)
The presentation summarizes the data regarding the pre-screening of those cognitive functions that are necessary for acquiring basic cultural techniques. The pre-screening done by the Special Needs Teacher in the examined institution applies to every first year pupil. The results and tendencies will be presented based on the selection of five classes over ten years. A comparison of the proportion between the pupils performing below and above the expected level will be shown, with regard to age and gender.